Analisis Pergeseran Paradigma Disiplin Kelas dalam Pendidikan Agama Islam: Dari Kurikulum Merdeka menuju Pendekatan Kurikulum Cinta - Fahmi, Ahmad Ghofur Al Wahidun; Syahid, Alya Syarfa Majda; Hunaida, Wiwin Luqna (Paedagogie, 2026)
The shifting educational paradigm in Islamic Religious Education (PAI) reflects an orientation toward character strengthening through a humanistic and student-centered approach. However, classroom discipline practices remain predominantly structural and administrative, limiting relational engagement and the internalization of compassion. This study aims to analyze the paradigm shift in classroom discipline from the Merdeka Curriculum framework toward the Love-Based Curriculum and to formulate a synthesis model for character development. This research employs a qualitative conceptual approach using a library research method. The analysis draws on scholarly articles published between ten years ago, retrieved from Google Scholar, DOAJ, and the Garuda portal, selected based on thematic relevance, journal indexing, and contextual alignment with Islamic education. Data were examined using content analysis and conceptual synthesis techniques. The findings indicate a shift from structural discipline toward relational and value-internalization-based discipline. While the Merdeka Curriculum provides pedagogical flexibility, the Love-Based Curriculum emphasizes empathy and respect for students’ dignity. Their synthesis results in a holistic discipline model that theoretically better supports religious character formation and personal responsibility.